A study of neurosis and occupation. Issue 2 (April 1973) - Ferguson, David
Abstract : Ferguson, D. (1973). British Journal of Industrial Medicine, 30, 187-198. A study of neurosis and occupation. Claims that male telegraphists in an Australian communications undertaking were unduly subject to neurosis and certain psychosomatic disorders as a result of the stress of their work were investigated by sickness absence and environmental and prevalence studies. The absence records of all telegraphists in the mainland capital city offices of the undertaking were compared with those of random samples of clerks and mechanics and, because of excess absence among sydney telegraphists, with those of mail sorters in that city. Subsequently, 516 telegraphists, 93% of those available in Sydney, Melbourne, and Brisbane, and 155 Sydney mail sorters (79% of a sample) were examined medically. Absence attributed to neurosis was much commoner in telegraphists than in the other occupations in each capital, and in Sydney telegraphists than in those of other capitals. Employees having such absence were more likely than others also to have uncertified and repeated absences, and absence attributed to bronchial and dyspeptic disorder and to injury. One-third (33%) of the 516 telegraphists examined were considered to have or to have had disabling neurosis, the prevalence being much greater in Sydney (44%) than in Melbourne (19%) or Brisbane (26%). The onset, course, associations, and other characteristics of neurosis are described. There was some evidence that the neurotic employee had increased liability to some other disorders but also that he was more likely to report ill health than others. Interpretation of increased other ill health in neurosis is confounded by the effects of an excess indulgence in habits. An increase in indices of mental stress was noted but some disorders commonly attributed to stress were not unduly prevalent in neurotics. Loss of craft status, monotony, dissatisfaction with job, fear of displacement by machine, group size, and supervisory practices were all thought to predispose to the high prevalence of neurosis in Sydney telegraphists. However, personal and social maladjustment was particularly evident in telegraphists in that city, and the population from which telegraphists were drawn may have been less well adjusted in Sydney than in Melbourne or Brisbane. Though it was possible in general to characterize the employee liable to neurosis, the predictive power of the characterization would be poor. The disorder followed no one pattern. Rather it appeared to be a collection of clinical syndromes which present as a result of the complex interaction of the personality with multiple factors at work and elsewhere over most of a lifetime. In individual subjects the relationship of stress at work to symptoms was usually ill defined, even in cases in which the identified probable factors were mainly or solely occupational. Nevertheless, there seems much to be gained from the establishment of mental health programmes in industry.